(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the positive effect of the moral potential of the civil servant in the management of the state and society on the development of the state is studied as a research goal. It has been analyzed from a business-philosophical point of view that in modern management, moral education is a means of producing and ensuring the performance of a complex program of activities that helps to increase the personal responsibility of employees. The socio-philosophical conclusions and results of the fact that public propaganda tools are largely dependent on personnel health and material spiritual education are revealed.